PROFIL PEMAHAMAN KONSEP SISWA KELAS VIII A SMP GKST IMANUEL PALU PADA MATERI BANGUN DATAR SEGIEMPAT - Lowo, Lilis Kartina; Sukayasa, Sukayasa; Hadjar, Ibnu (Universitas Tadulako, 2025)
This research aims to obtain a description of the conceptual understanding profile of class VIII A students at GKST Imanuel Palu Middle School. This type of research is descriptive research. The subjects of this research were students with high, medium and low mathematics abilities. Data collected by interviews and giving assignments. The results of this research show that students with high abilities: (1) can state the definition of a rhombus, but cannot state the definition of a kite and parallelogram. (2) can classify flat shapes that have an axis of symmetry and those that do not have an axis of symmetry. (3) can solve the story problems given. Students with moderate mathematical abilities; (1) It is not appropriate to state the definition of a rhombus, because the definition given by the student is the definition of a kite. (2) can group flat shapes that do not have an axis of symmetry (3) can apply the formula for the perimeter of a parallelogram, but have not yet found the final result of the story problem. Students with low mathematical abilities: (1) have not met the indicators, because the subject did not write the definitions of kite, parallelogram and rhombus. (2) Subjects can group flat shapes that have an axis of symmetry. (3) the subject cannot solve the story problems.